Mencegah Gejolak Keuangan dengan Manajemen Risiko Likuiditas Perbankan - Ika Permatasari (BISMA (Bisnis dan Manajemen), 2018)
Sound liquidity risk management is needed to deal with the impact of liquidity risk that can bring contagion effects that threatens the financial system stability of a country. This study aims to analyze the necessary issues in liquidity risk management in Indonesia, which emphasized on four pillars. The main pillars of the bank's liquidity risk management include active oversight board of commissioners and directors; policies, procedures, and liquidity risk limits; liquidity risk management process; and internal control systems.